Development of Inquiry Based E-Module on Water Cycle Topic for Class V Elementary School Students - Tri Andini, Aprilia; Rohana; Treny Hera (SEMESTA: Journal of Science Education and Teaching, 2024)
The research aims to develop e-modules based on inquiry learning on water cycle material that is valid, practical and effective. This type of research is research and development (R&D) using the ADDIE development model which consists of 5 stages, namely Analyze, Design, Development, Implementation, Evaluation. The subjects in this research were 3 expert validators, 2 expert validators, lecturers, 1 class teacher and class V students at SD Negeri 152 OKU. The data collection instruments used were validation questionnaires to validators, student response questionnaires, and test questions. Based on the results of the assessment research from 3 validators, namely 2 validator experts and 1 teacher, it shows that the quality of the e-module product is very valid with a score percentage of 88.8%. The level of practicality after being tested on students meets the very practical criteria with a score percentage of 91%. The results of the ability test questions are in the very good category with an average score of 87.5%. So the results of developing e-modules based on inquiry learning on criteria are very effective for use in science learning, especially in water cycle material for class V elementary schools.Keywords: E-module, Inquiry Based Learning, Water Cycle